Bakiak peningkat nilai pencasila melalui metode belajar pembelajaran - FAUZIL'ADHIM, MOHAMMAD FATAHILLAH (Maliki Interdisciplinary Journal, 2024)
The principle of Pancasila contained in the traditional bakiak game lies in the third principle of unity where the bakiak game creates an attitude of mutual cooperation, toleration, and as a manifestation of the development of noble cultural values. The concept of mutual cooperation can be applied to the game by dividing players into teams that carry and transport sacks from one team to another. carrying and transporting sacks from one location to another by cooperating with each other. This will increase the value of co-operation and unity among the participants. By applying the concepts of Pancasila to the bakia game, participants can learn values that are important for the development of good character and personality, such as cooperation, justice, morality, unity, and just and civilised humanity. Bakia games can also be a fun and effective method to introduce Pancasila values to children and the general public